2014
DOI: 10.1093/infdis/jiu626
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Polyomaviruses in Men: The HPV Infection in Men (HIM) Study

Abstract: MCPyV infection is highly prevalent in adults, with age and race being predisposing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 39 publications
6
32
3
Order By: Relevance
“…Indeed, Pedergnana et al found indication for TSPyV transmission from parents to children, and between siblings. Currently the mechanism for transmission of HPyV9 remains unidentified; however, Karachaliou et al identified younger age at day‐care entry as risk factor . Alternatively, household/family members might share genetic risk factors and glycan receptors relevant for these viruses, for example, the acquisition of the HPyV9 glycan receptor ligand, which Khan et al speculated to be acquired through the consumption of red meat and milk.…”
Section: Discussioncontrasting
confidence: 84%
“…Indeed, Pedergnana et al found indication for TSPyV transmission from parents to children, and between siblings. Currently the mechanism for transmission of HPyV9 remains unidentified; however, Karachaliou et al identified younger age at day‐care entry as risk factor . Alternatively, household/family members might share genetic risk factors and glycan receptors relevant for these viruses, for example, the acquisition of the HPyV9 glycan receptor ligand, which Khan et al speculated to be acquired through the consumption of red meat and milk.…”
Section: Discussioncontrasting
confidence: 84%
“…HPyV9 was identified in a serum sample from a kidney transplant patient and in the skin of a patient with Merkel cell carcinoma (Sauvage et al, 2011;Scuda et al, 2011). The presence of HPyV9 DNA was confirmed in 21 serum specimens of 101 kidney transplant patients, in PBMCs of an AIDS patient and in skin from a healthy person (Hampras et al, 2015;Lednicky et al, 2014;van der Meijden et al, 2014). HPyV10 isolate MW was originally isolated from faeces (Siebrasse et al, 2012a), while isolate 10ww was first described in skin from a patient with warts, hypogammaglobulinaemia, infections and myelokathexis (WHIM) syndrome .…”
Section: Introductionmentioning
confidence: 80%
“…MCPyV, HPyV6, HPyV7, TSPyV, HPyV9, HPyV10 and STLPyV, but not the other HPyVs have been found in skin (Bellaud et al, 2014;Fischer et al, 2012;Giraud et al, 2008;Hampras et al, 2015;Ho et al, 2015;Imajoh et al, 2013;Pastrana et al, 2013a;Ramqvist et al, 2014;Sauvage et al, 2011;Schowalter et al, 2010;Schrama et al, 2014;Urbano et al, 2014;van der Meijden et al, 2010;Wanat et al, 2012;Wieland et al, 2014). BKPyV, which is not common in the skin , had in general higher early and late promoter activity than most of these viruses in skin-derived A375, A431 and HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations